Pemerintahan Kolaboratif Sebagai Solusi Kasus Deforestasi di Pulau Kalimantan: Kajian Literatur: Collaborative Governance as Solution for Deforestation Case in Kalimantan Island: A Literature Review - Cahyoko Edi Tando; Sudarmo Sudarmo; Rina Herlina Haryanti (Pusjar SKPP Lembaga Administrasi Negara, 2019)
Indonesia is a country with the largest biodiversityin the world. It has a rich forest both in land and the surface of the land, however the forest-related problemalso occurs in Indonesia. One of the largest islands in the world, namely Kalimantan Island has the largest forest distribution in Indonesia. In fact, it cannot be separated from deforestation issue for plantation, mining, and new residential areas reasons. If there is no monitoring, derforestation will produce increasingly severe forests damage, global climate change, and conservation of native animals in the forest. Collaborative governance is chosen as a means toovercomeg the problem of deforestation, and cooperate to other actors related to the community and jointly reducing this deforestation. Collaborative governance is considered capable to solve problem, especially from actors from the plantantion and mining business sector Further, the expected correlation is to be able to work together without being harmed. Keywords: Deforestation, Kalimantan Island, and Collaborative Governance Abstrak Indonesia merupakan negara dengan kenanekaragaman hayati terbesar di dunia, memiliki hutan yang kaya kandungan di dalam tanah maupun yang di permukaan tanah, namun permasalahan akan hutan pun tidak menutup bahwa juga terjadi di Indonesia, salah satu pulau terbesar di dunia yakni Pulau Kalimantan memiliki persebaran hutan terbesar di Indonenesia, tidak lepas dari deforestasi baik untuk alasan perkebunan, pertambangan, dan kawasan hunian baru. Deforestasi jika di biarkan terus menerus akan mengakibatkan kerusakan hutan yang semakin parah, perubahan iklim dunia, dan mengancam hewan asli yang ada di dalam hutan tersebut. Pemerintahan kolaboratif di pilih sebagai sarana untuk mengatasi permasalahan deforestasi ini bekerjasama dengan aktor lain yakni swasta dan masyarakat untuk bersama-sama mengurangi deforestasi ini. Pemerintahan kolaboratif dianggap mampu dalam menyelesaikan permasalahan terutama dari para aktor dari sektor usaha perkebunan maupun pertambangan, korelasi yang di harapkan adalah bisa saling bekerjasama tanpa ada yang dirugikan. Kata Kunci: Deforestasi, Pulau Kalimantan, dan Pemerintahan Kolaboratif